65. Peripheral nerve ultrasonography: Clinical use. Issue 1 (January 2015) - Tozzi, M.C.; Turri, M.; Concon, E.; Cavallaro, T.; Fabrizi, G.M.; Monaco, S.; Bertolasi, L.
<x xml:space="preserve">Abstract</x> Charcot–Marie–Tooth disease (CMT) is an heterogeneous group of hereditary neuropathies characterized by weakness and atrophy of the limbs, loss of sensation and absent or reduced tendon reflexes. Chronic Inflammatory Demyelinating Polyneuropathy (CIDP) causes progressive or recurrent weakness and numbness of the limbs. Both CMT and CIDP share similar nerve conduction study abnormalities (reduced amplitude of sensory and motor potentials, and reduced conduction velocity). The aim of our study was to compare the ultrasound (US) data recorded in genetic neuropathy (CMT) and inflammatory neuropathy (CIDP). We enrolled 10 patients with CMT type 1A and 10 patients with CIDP. In this study we compared left and right median nerve cross-sectional area (CSA) and echogenicity nerve in the forearm, between two groups of patients to evaluate a possible difference. Three US classes were identified based on CSA and echogenicity. For all patient included neurophysiological assessment was used to estimate a possible correlation between the nerve conduction study variables and US data. US of the nerve can be a tool of significant value in the differential diagnosis in different neuropathies.